2021
DOI: 10.1101/2021.02.25.432623
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A functional logic for neurotransmitter co-release in the cholinergic forebrain pathway

Abstract: The forebrain cholinergic system has recently been shown to co-release both acetylcholine and GABA. We have discovered that such co-release by cholinergic inputs to the claustrum differentially affects neurons that project to cortical versus subcortical targets. The resulting changes in neuronal gain toggles network efficiency and discriminability of output between two different projection subcircuits. Our results provide a potential logic for neurotransmitter co-release in cholinergic systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 37 publications
2
14
0
Order By: Relevance
“…The excitatory responses to cholinergic input observed by Nair et al (2021) were monosynaptic and mediated by nAChRs, in line with the high expression of nAChRs in the claustrum noted above (Winzer-Serhan and Leslie, 2005). Nair et al (2021) observed that inhibitory cholinergic input received by cortexprojecting claustral neurons was also monosynaptic but was produced by a surprising co-release of ACh and GABA by the basal forebrain. Thus, depending on their projection targets, claustrum neurons receive opposing excitatory and inhibitory input from the basal forebrain.…”
Section: Cholinergic Modulation Of the Claustrum Microcircuitsupporting
confidence: 58%
See 4 more Smart Citations
“…The excitatory responses to cholinergic input observed by Nair et al (2021) were monosynaptic and mediated by nAChRs, in line with the high expression of nAChRs in the claustrum noted above (Winzer-Serhan and Leslie, 2005). Nair et al (2021) observed that inhibitory cholinergic input received by cortexprojecting claustral neurons was also monosynaptic but was produced by a surprising co-release of ACh and GABA by the basal forebrain. Thus, depending on their projection targets, claustrum neurons receive opposing excitatory and inhibitory input from the basal forebrain.…”
Section: Cholinergic Modulation Of the Claustrum Microcircuitsupporting
confidence: 58%
“…Optogenetic activation of cholinergic axons indicated that claustral neurons receive cholinergic input in a cell-type specific manner: cortex-projecting claustrum neurons were primarily inhibited, while claustrum neurons projecting to subcortical structures (including thalamus and habenula) and vasointestinal peptide (VIP) expressing interneurons in the claustrum were excited. The excitation of VIP interneurons in the claustrum mirrors observations in the cortex (Fu et al, 2014), with the notable exception that cholinergic input did not excite somatostatin (SST) expressing interneurons or parvalbumin (PV) expressing interneurons in the claustrum (Nair et al, 2021) but does excite these interneurons in the cortex.…”
Section: Cholinergic Modulation Of the Claustrum Microcircuitmentioning
confidence: 63%
See 3 more Smart Citations